(untitled) (Research, Society and Development, 2020)
The objective of this study was to determine and analyze the economic loss from the main causes of condemnations (total) of swine carcasses in slaughterhouses inspected by the Federal Inspection Service in the state of Santa Catarina from 2010 to 2018. Economic loss was calculated by multiplying the number of carcasses condemned (total) by the mean meat yield per carcass and the mean annual price per kilogram of pork and monetary values were updated for the year 2018 using the IGP-DI. The results indicated an economic loss of R 1.65 billion for condemnations (total) of swine carcasses, the main causes being contamination (R 481.67 million), nephritis (R 508.42 million), urinary cyst (R 229.05 million), pericarditis (R 111.65 million) and larval migration (R 217.16 million). The principal associated factors for the occurrence of condemnations (total) of swine carcasses are operational failures that occurred during the evisceration stage and the occurrence of parasitic or infectious diseases in animals. Therefore, it is recommended to adopt good production practices and train slaughterhouse employees, in order to minimize such losses in pork production of Santa Catarina.